Academic Services in Islamic Education Management Study Program: The Actualization of the Basic Values of the State Civil Apparatus at IAIN Palopo - Burhan Rifuddin; Dodi Ilham; Nurdin K (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This research aims to develop the MPI study program 's academic information to improve the efficiency and effectiveness of education services by web-based information systems by updating the State Civil Establishment (ASN) values, using the approach of Participatory Action Research (PAR). The solution to the issue of web-based academic services in IAIN Palopo 's Islamic Education Management Study Programme, namely 1) conducting consultations related to web design of the Islamic Education Management Study Programme; 2) registering the web sub - domain and collecting materials that will be the content of the Islamic Education Management Study Program web.; 3) Installing web-based machines in registered sub-domains and creating a web-based framework for the Islamic Education Management Study Program; 4) designing a web-based display of the Islamic Education Management Study Program; 5) making menus and filling each menu with types of services, information, and activities related to the Islamic Education Management Study Program; 6) Implementation of web management training for prospective web administrators of Islamic Education Management Study Program; 7) Automation of web services published in the Islamic Education Management Study Program.